Modeling and Analysis of Cross-Session Search Tasks - Kotov, Alexander; Bennett, Paul; White, Ryen W.; Dumais, Susan; Teevan, Jaime (Proceedings of SIGIR 2011, 2011)
The information needs of search engine users vary in complexity, depending on the task they are trying to accomplish. Some simple needs can be satisfied with a single query, whereas others require a series of queries over a longer period of time. While search engines effectively satisfy many simple needs, searchers receive little support when their information needs span sessions. In this work, we propose methods for modeling and analyzing user search behavior that extends over multiple search sessions. We focus on two problems: (i) given a user query, identify all related queries from previous sessions that the user has issued, and (ii) given a multi-query task for a user, predict whether the user will return to this task in the future. We model both problems within a classification framework that uses features of individual queries and long-term user search behavior at different granularity. Experimental evaluation of the proposed models for both tasks indicates that it is possible to effectively model and analyze cross-session search behavior. Our findings have implications for improving search for complex information needs and designing search engine features to support cross-session search tasks.